A guide to MATLAB object-oriented programming - Register, Andy H. (Chapman & Hall/CRC, 2007)
This is the first book to deliver broad coverage of the documented and undocumented object-oriented features of MATLAB (R). Unlike the typical approach of other resources, this guide explains why each feature is important, demonstrates how each feature is used, and promotes an understanding of the interactions between features.